2019
DOI: 10.1016/j.curtheres.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Developmental Effects of Isotretinoin (Retinoid) Treatment for Acne Vulgaris

Abstract: Highlights Isotretinoin teratogenicity well established; psychiatric effects documented, controversial Disturbed retinoid signaling implicated in isotretinoin teratogenic and psychiatric effects Effect of genetics on susceptibility to psychiatric side effects is possible, not yet known Postnatal neurocognitive effects of isotretinoin not yet established

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…Isotretinoin is a teratogen; there is about a 20–35% risk for congenital defects in infants exposed to the drug in the uterus, and about 30–60% of children exposed to isotretinoin prenatally have been reported to show neurocognitive impairment ( Choi et al, 2013 ). Studies showed that the teratogenic effect of isotretinoin was associated with a wide spectrum of birth defects including craniofacial, heart, and nervous system malformation as well as psychomotor retardation, mental retardation, learning disabilities, and premature birth ( Suuberg, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isotretinoin is a teratogen; there is about a 20–35% risk for congenital defects in infants exposed to the drug in the uterus, and about 30–60% of children exposed to isotretinoin prenatally have been reported to show neurocognitive impairment ( Choi et al, 2013 ). Studies showed that the teratogenic effect of isotretinoin was associated with a wide spectrum of birth defects including craniofacial, heart, and nervous system malformation as well as psychomotor retardation, mental retardation, learning disabilities, and premature birth ( Suuberg, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our findings indicated DGCs as a potential cellular target for the direct alleviation of RA-induced depression. A significant body of evidence indicates that chronic 13-cis-RA administration is involved in both clinical depression and animal models of depression [5,[10][11][12][13]37]. Clinically, 13-cis-RA is a highly effective drug for severe acne but is associated with depression and suicide, which has attracted major attention for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to primary depression, secondary depression can be caused by specific reasons, including organic diseases, psychotic disorders, medications, and so on [5][6][7][8][9]. It has been reported that treatment with the anti-acne drug Accutane (isotretinoin, 13-cis-retinoic acid [13-cis-RA]) has been associated with severe depression and even suicide [5,[10][11][12][13]. For all drugs, Accutane ranks fourth in the top five medications with the most frequent reports of depression [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence base for severe neuropsychiatric outcomes is mixed and inconclusive. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] For example, isotretinoin has been associated with both increased 14 and reduced 16 risk of depression.…”
mentioning
confidence: 99%
“…In addition, severe neuropsychiatric outcomes, such as anxiety, depression, suicidal ideation, self‐harm and completed suicide, have been reported. However, the evidence base for severe neuropsychiatric outcomes is mixed and inconclusive 9–22 . For example, isotretinoin has been associated with both increased 14 and reduced 16 risk of depression.…”
mentioning
confidence: 99%